Analysis of te Effect of Human Resources on Company Performance in Baznas Jember - Ahmad faizal; Dianidza Arodha; Akhmad Afandi (Journal of Islamic Economics Perspectives, 2020)
Indonesia is a country where the majority of the population is Muslim and is the country with the largest Muslim population in the world, with a percentage of 87.2% of Indonesia's population, which amounts to around 271.066 million in 2020, with a large number of Muslim population in Indonesia making it easier to minimize or eradicate the number of poverty in Indonesia through programs carried out by the National Amil Zakat Agency (BAZNAS). This research is a quantitative explanatory research using Multiple Linear Regression which was developed with Path Analysis and Trimming Theory. Hypothesis testing with the help of software (SPSS) version 22. The results of the analysis show that human resource variables have no significant effect on company performance, with (Standardized Coefficients) 0.082 (8.20%) positive.